Joining of Graphite to Ti6Al4V Alloy Using Cu‐Based Fillers. Issue 11 (17th September 2019) - Duan, Yu; Mao, Yangwu; Xu, Zhemi; Deng, Quanrong; Wang, Geming; Wang, Shenggao
Abstract : Joining of graphite to Ti6Al4V (TC4) alloy is achieved with three Cu‐based fillers (Cu‐22TiH2, Cu‐50TiH2, and Cu‐30TiH2 ‐5Ni). Microstructural characterizations reveal that a thin TiC layer and a diffusion layer containing Ti solid solution (Ti(ss)) with Ti2 Cu are developed at the graphite/filler layer and filler layer/TC4 interfaces, respectively. For the joint obtained with Cu‐22TiH2 filler, the filler layer consists of TiCu and Ti2 Cu, whereas it is composed of Ti2 Cu, TiCu, and Ti(ss) for the joint with Cu‐50TiH2 filler. In the case of the joint with Cu‐30TiH2 ‐5Ni filler, the filler layer mainly contains Ti(Cu, Ni) and Ti2 (Cu, Ni). The microhardness of the interfacial area in the joints is highly related to the microstructure of joints. The filler layer of the joint with Cu‐50TiH2 filler exhibits higher microhardness than those with Cu‐22TiH2 and Cu‐30TiH2 ‐5Ni fillers, owing to the high content of Ti2 Cu phase with relatively high microhardness and the increase in hardness of Ti‐Cu intermetallics at higher brazing temperatures. The high shear strength of joints reveals favorable bonding of Cu‐based fillers with substrates. Abstract : Joining of graphite to Ti6Al4V alloy is achieved with three Cu‐based fillers (Cu‐22TiH2, Cu‐50TiH2, and Cu‐30TiH2 ‐5Ni). Microstructural and mechanical characterizations of joints are performed. The microhardness of the interfacial area in the joints is highly related to the microstructure of joints. The high shear strength of joints reveals favorable bonding of Cu‐based fillers with substrates.